Shifts in sulphur-cycling bacteria in the rhizobiome support the adaptation of Caulerpa prolifera to elevated sulphide levels - Barilo, Anastasiia; Engelen, Aschwin; Wilken, Susanne; Bouwmeester, Harro; Muyzer, Gerard (Frontiers in Marine Science, 2024)
Caulerpa is a genus of green macroalgae that lives in tropical and subtropical coastal waters. It is an intriguing organism because, despite having plant-like structures, it is one giant cell – which, next to multiple nuclei, chloroplasts, and mitochondria, also contains endo- and epiphytic bacteria. The role of these bacteria is unknown, but they might impact the growth and development of the host, adaptation to environmental parameters, and, hence, the ecological success of these algae. We hypothesised that increased sulphide concentrations would trigger a significant shift in the microbial community composition associated with C. prolifera rhizoids, favouring sulphide-oxidizing bacteria. To test this hypothesis, we conducted a mesocosm experiment incubating C. prolifera in sediments with different sulphide concentrations and analysed the algal photosynthesis, growth, and microbiome composition. While photosynthesis was not affected, the Caulerpa weight-based growth rate decreased linearly with increasing sulphide concentration. To analyse the microbiome, we extracted DNA and RNA from the fronds, rhizoids, and the accompanying sediments and performed 16S amplicon sequencing. The microbiome of the fronds was unaffected in both the DNA and RNA samples. However, an increase in sulphide concentration coincided with a decrease in the relative abundance of sulphate-reducing bacteria associated with Caulerpa rhizoids, particularly from the family Desulfocapsaceae. In the RNA samples, potential sulphide oxidisers of the rhizoid-associated members of the Beggiatoaceae were detected. Our results suggest that the rhizobiome of Caulerpa plays a significant role in its adaptation to sulphide-rich environments, offering new insights into the complex interactions within marine holobionts.